Investigating flow theory in the young choral academy community choir - Goh, Darlyn Lee Ee (2018)
Choral education in Malaysia remains its infancy in comparison with countries such as the USA, Australia and Germany which have established choral music education, performance context and community activities. However, Malaysia’s local choral industry has experienced a relatively recent increase in activity in the past decade seen through rising numbers of amateur choirs and performances. Although choral music researchers have studied the motivations and understanding of values related to choral music participation and the function of choral activities, those types of efficacy studies have yet to be implemented among Malaysian choral groups. Apart from that, the process of knowledge transfer between choral conductors and choirs tends to occur in private music institutions rather than in public schools. One such private institution that serves as a case study for this research on choral music transmission is the Young Choral Academy (YCA) which is first academy for choral music in Malaysia. Founded in 2002 and directed by Susanna Saw and Mak Chi Hoe, the Young Kuala Lumpur Singers (YKLS) is an award-winning community choir comprising of approximately forty members formed under YCA. Having produced seventeen concert productions to date, the choir members’ devotion to singing suggests that the activity provides a form of gratification that engenders dedication.